FACTORS OF STUDENTS’ DEMOTIVATION IN ATTENDING BILINGUAL CLASS IN IAIN PURWOKERTO - Muflihah Muflihah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
This research was aimed at revealing factors of students demotivation in attending bilingual class in IAIN Purwokerto. This research was driven by the fact that some students were found proposing themselves to quit from the bilingual class. In addition, some others seemed reluctant to attend the lectures. This condition showed that they were demotivated in attending the bilingual class. This research is a survey study using a quantitative approach. The data of this research were gained through questionaire using total class sampling. Among 393 respondents of bilingual class students, 309 of them returning the questionaire. Respondents were asked two questions, one of which was a closed-ended question, asking whether they had ever experienced a feeling of demotivation. The other question is an open-ended question, asking the factors causing their feeling of demotivation. Students are allowed to give more than one answers. Data were analyzed using descriptive statistics analysis, counting the presentage of each factor. This research found that there are 8 factors causing students’ demotivation in attending bilingual class, i.e. (1) lack of language ability (228 respondents, equals to 73.79%); (2) language experience (34 respondents, equals to 11.0%); (3) lecturer factor (21 respondents, equals to 6.80%); (4) task factor (18 respondents, equals to 5,83%); (5) lack of interest (17 respondents, equals to (5.50%); (6) environment factor (13 respondents, equals to 4.21%) (7) Friend factor (4 respondent, equals to 1.29%); and (8) facilities (2 respondents, equals to 0.65%).